HnRNPR-CCNB1/CENPF axis contributes to gastric cancer proliferation and metastasis - Chen, Er-Bao (Aging (Albany NY), 2019)
Gastric cancer (GC) is a common disease globally with high mortality rate. It is therefore necessary to develop novel therapies targeting specific events in the pathogenesis of GC. Some hnRNP family members are involved in multiple cancer biological behaviors. However, the potential function and mechanism of hnRNPR, a new molecule of hnRNP family in GC remains unknown. We found that the expression of hnRNPR was significantly overexpressed in multiple cancers compared to the normal tissues. Functionally, hnRNPR promoted cancer cell proliferation, migration, and invasion. Knockdown of hnRNPR in two type mice models, with two types of tumors models decreased the tumor aggressiveness and metastasis. Mechanistically, hnRNPR targeted oncogenic pathways by stabilizing the expression of CCNB1 and CENPF mRNA level. Knockdown of CCNB1 and CENPF abolished the hnRNPR-induced cell growth and invasion, respectively. Furthermore, the protein level of hnRNPR in the tumor was positively correlated with the expression of CCNB1 and CENPF in clinical samples. Together, these results indicate that overexpression of hnRNPR promoted the aggressiveness of GC by increasing the mRNA expression of CCNB1 and CENPF. HnRNPR-CCNB1/CENPF axis may be a potential therapeutic target for GC treatment.